The double impact of institutions: Institutional spillovers and entrepreneurial activity in the solar photovoltaic industry - Hoppmann, Joern; Vermeer, Ben (Journal of Business Venturing, 2020)
We investigate whether and when institutional spillovers, i.e., institutional effects across national borders, drive domestic entrepreneurial activity. Drawing on data on venture capital (VC) investments in the solar photovoltaic industry, we provide evidence for institutional spillovers and demonstrate that they are moderated by the presence of domestic institutions and the institutional distance between domestic and foreign policy schemes. By showing that domestic institutions not only influence entrepreneurial activity directly, but also facilitate spillovers, our findings demonstrate a double impact of institutions. Overall, we contribute to the literatures on the drivers of VC investments, institutions and entrepreneurship, and environmental entrepreneurship.